Sensitivity analysis of the botulism surveillance system in Spain between 1997 and 2019 (Boletín Epidemiológico Semanal, 2023)
Introduction: botulism is a low-incidence but severe disease able to cause outbreaks. Autonomous Provinces and Cities notify possible, probable and confirmed cases to the National Epidemiological Surveillance Network (RENAVE by its acronym in Spanish), managed by the National Centre for Epidemiology (CNE in Spanish). The aim of this study was assess the sensitivity of the botulism (food-borne, infant and wound related) surveillance system.Method: the capture-recapture methodology was employed using as sources of information all cases in the RENAVE database and those cases in the Minimum Basic Data Set (CMBD by its acronym in Spanish) with botulism as the main diagnosis. Due to methodological changes in the CMBD, study period was divided into two parts: 1997-2015 and 2016-2019. Matched cases were identified using common variables: date of birth, sex and date and province of hospitalisation. Total number of cases was calculated by using Chapman-Seber method. Cases included in the CMBD but missing from the RENAVE were analysed in a complementary study using information from other sources. Results: RENAVE sensitivity was 64,4% and 78,7% for food-borne botulism each period, being lower than that achieved by CMBD. For infant botulism, RENAVE was more sensitive than CMBD in the second period, reaching a level close to 90%. No woud-related cases were identified in RENAVE.Conclusions: The sensitivity of RENAVE increased during the second period although individualised reporting cases needs to be strengthened to reduce case loss.
Keywords: botulism; epidemiological surveillance; capture-recapture